Cryopreserved vitamin D(3)-tolerogenic dendritic cells pulsed with autoantigens as a potential therapy for multiple sclerosis patients - Mansilla, María José (J Neuroinflammation, 2016)
BACKGROUND: Tolerogenic dendritic cells (tolDC) have been postulated as a potent immunoregulatory therapy for autoimmune diseases such as multiple sclerosis (MS). In a previous study, we demonstrated that the administration of antigen-specific vitamin D(3) (vitD3) tolDC in mice showing clinical signs of experimental autoimmune encephalomyelitis (EAE; the animal model of MS) resulted in abrogation of disease progression. With the purpose to translate this beneficial therapy to the clinics, we have investigated the effectivity of vitD3-frozen antigen-specific tolDC pulsed with myelin oligodendrocyte glycoprotein 40-55 peptide (f-tolDC-MOG) since it would reduce the cost, functional variability and number of leukapheresis to perform to the patients. METHODS: Mice showing EAE clinical signs were treated with repetitive doses of f-tolDC-MOG. Tolerogenic mechanisms induced by the therapy were analysed by flow cytometry and T cell proliferation assays. RESULTS: Treatment with f-tolDC-MOG was effective in ameliorating clinical signs of mice with EAE, inhibiting antigen-specific reactivity and inducing Treg. In addition, the long-term treatment was well tolerated and leading to a prolonged maintenance of tolerogenicity mediated by induction of Breg, reduction of NK cells and activation of immunoregulatory NKT cells. CONCLUSIONS: The outcomes of this study show that the use of antigen-specific f-tolDC promotes multiple and potent tolerogenic mechanisms. Moreover, these cells can be kept frozen maintaining their tolerogenic properties, which is a relevant step for their translation to the clinic. Altogether, vitD3 f-tolDC-MOG is a potential strategy to arrest the autoimmune destruction in MS patients.